Screening for target toxins of the antiophidic protein DM64 through a gel-based interactomics approach - Rocha, Surza Lucia Gonçalves (2017)
DM64 is a glycosylated protein with antivenomactivity isolated fromthe serum of the opossumDidelphis aurita. It binds non-covalently to myotoxins I (Asp49) and II (Lys49) from Bothrops asper venom and inhibits their myotoxic effect. In this study, an affinity columnwith immobilizedDM64 as baitwas used to fish potential target toxins. All ten isolated myotoxins tested were able to effectively bind to the DM64 column. To better access the specificity of the inhibitor, crude venoms from Bothrops (8 species), Crotalus (2 species) and Naja naja atra were submitted to the affinity purification. Venom fractions bound and nonbound to the DM64 columnwere analyzed by two-dimensional gel electrophoresis andMALDI-TOF/TOFMS. Although venomfractions bound to the column were mainly composed of basic PLA2, a few spots corresponding to acidic PLA2 were also observed. Some unexpected protein spotswere also identified: C-type lectins and CRISPmay represent putative new targets forDM64, whereas the presence of serine peptidases in the venom bound fraction is likely a consequence of nonspecific binding to the column matrix. The present results contribute to better delineate the inhibitory potential of DM64, providing a framework for the development of more specific antivenom therapies. Biological significance: Local tissue damage induced bymyotoxic PLA2 remains a serious consequence of snake envenomation, since it is only partially neutralized by traditional antivenom serotherapy. Myotoxin inhibition by highly specific molecules offers great promise in the treatment of snakebites, a health problemlargely neglected by governments and pharmaceutical industries. Bioactive compounds such as DM64 can represent a valuable source of scaffolds for drug development in this area. The present study has systematically profiled the binding specificity of DM64 toward a variety of snake venom toxin classes and therefore can lead to a better understanding of the structure-function relationship of this important antivenom protein.